An interactive game for rehabilitation based on real-time hand gesture recognition - Chen, Jiang; Zhao, Shuying; Meng, Huaning; Cheng, Xu; Tan, Wenjun (Frontiers in Physiology, 2022)
Now Cardiovascular and cerebrovascular diseases have become serious global health problems since their high incidence and fatality rate. Some patients with cardiovascular cerebro-Cardiovascular diseases even may face motor or cognitive dysfunction after surgery. In recent years, human-computer interactive systems with Artificial Intelligence (AI) have become an important part in human well-being as it enables novel forms of rehabilitation therapies. We propose an interactive game utilizing real-time skeleton-based hand gesture recognition. It aims to assist rehabilitation exercises by improving the hand-eye coordination of the patients during a gamelike experience. For this purpose, we propose a light residual graph convolutional architecture for hand gesture recognition. Further, we design the whole system using the proposed gesture recognition module and some third-party modules.